2017
DOI: 10.3390/molecules22050821
|View full text |Cite
|
Sign up to set email alerts
|

From Cell to Beak: In-Vitro and In-Vivo Characterization of Chicken Bitter Taste Thresholds

Abstract: Bitter taste elicits an aversive reaction, and is believed to protect against consuming poisons. Bitter molecules are detected by the Tas2r family of G-protein-coupled receptors, with a species-dependent number of subtypes. Chickens demonstrate bitter taste sensitivity despite having only three bitter taste receptors—ggTas2r1, ggTas2r2 and ggTas2r7. This minimalistic bitter taste system in chickens was used to determine relationships between in-vitro (measured in heterologous systems) and in-vivo (behavioral) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…In the present study, the chicks showed aversion to bitter solutions concentration-dependently, and the concentrations at which the chicks' solution intakes of QHCl and DHCl started to decrease match those observed in our previous behavioral studies (Kudo et al 2010a;Hirose et al 2015). In addition, QHCl was reported to demonstrate a 30-times increase for the in vivo avoidance versus in vitro detection threshold in chickens (Cheled-Shoval et al 2017), and this observation matches our results. According to the present study, the discrepancy of the results between in vivo avoidance and in vitro detection of QHCl in chickens is considered to be derived from the inhibition of TRPM5 by QHCl itself.…”
Section: Real-time Quantitative Reverse Transcription Pcrsupporting
confidence: 92%
“…In the present study, the chicks showed aversion to bitter solutions concentration-dependently, and the concentrations at which the chicks' solution intakes of QHCl and DHCl started to decrease match those observed in our previous behavioral studies (Kudo et al 2010a;Hirose et al 2015). In addition, QHCl was reported to demonstrate a 30-times increase for the in vivo avoidance versus in vitro detection threshold in chickens (Cheled-Shoval et al 2017), and this observation matches our results. According to the present study, the discrepancy of the results between in vivo avoidance and in vitro detection of QHCl in chickens is considered to be derived from the inhibition of TRPM5 by QHCl itself.…”
Section: Real-time Quantitative Reverse Transcription Pcrsupporting
confidence: 92%
“…Even though ggTas2rs appear to be promiscuous and tend to accommodate many chemically diverse compounds, bitter compounds may exhibit different selectivity/promiscuity profiles toward chicken bitter taste receptors, and can be very selective for a specific subtype (Behrens et al, 2014 ). So far, a total of 25 bitter agonists for the three chicken Tas2rs and an antagonist for ggTas2r1 and ggTas2r7 have been unraveled (Behrens et al, 2014 ; Hirose et al, 2015 ; Dey et al, 2016 ; Cheled-Shoval et al, 2017 ). We took advantage of the simple ggTas2r system to compare in vitro vs. in vivo detection thresholds of selective and promiscuous ggTas2r agonists.…”
Section: Introductionmentioning
confidence: 99%
“…We took advantage of the simple ggTas2r system to compare in vitro vs. in vivo detection thresholds of selective and promiscuous ggTas2r agonists. In general, in vivo thresholds were similar or up to two orders of magnitude higher than the in vitro ones, but the in vivo : in vitro ratios were different for different ligands and ggTas2r-promiscuous ligands did not exhibit lower ratios than ggTas2r-selective ligands (Cheled-Shoval et al, 2017 ). Recently, integrating in silico and in vitro experiments on ggTas2r1 we investigated the binding modes of known agonists into the binding site and predicted additional ligands, providing a docking strategy for chemosensory receptors and other GPCRs, where the sequence identity between models and templates is very low (Di Pizio et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The possible ways of identifying (or confirming computationally predicted) agonists of chemosensory receptors include: (i) screening of cells that heterologously express a single taste receptor [ 14 , 18 , 57 ]; (ii) quantifying licking or consumption animal tests [ 58 , 59 ]. This latter behavioral testing method relies on the similarity of the taste systems in different organisms.…”
Section: Biomimetic Sensors For Taste and Odor Sensation Mechanismmentioning
confidence: 99%